Strong unique ergodicity of random dynamical systems on Polish spaces - Płonka, Paweł (Annales Mathematicae Silesianae, 2016)
In this paper we want to show the existence of a form of asymptotic stability of random dynamical systems in the sense of L. Arnold using arguments analogous to those presented by T. Szarek in [6], that is showing it using conditions generalizing the notion of tightness of measures. In order to do that we use tightness theory for random measures as developed by H. Crauel in [2].